A survey evaluating knowledge, perception, and use of skin lightening products among South African students - Farzana Rahiman, PhD; Lester M. Davids, PhD; Amy Thomas, Hons (Wolters Kluwer, 2021)
Background: In sub-Saharan Africa, the use of skin-lightening products (SLPs) for cosmetic purposes has become common practice among women with dark skin tones. Despite the associated risks, the practice is still significantly increasing in Africa. The objective of this study was to determine the knowledge, perceptions and practice toward skin lightening among young adults. Methods: A cross-sectional survey among health science students at a tertiary institution in the Western Cape of South Africa was conducted. Results: A total of 401 participants were included in the sample. There was a low prevalence (12%) of skin-lightening practice among students, which could possibly be a result of students being aware of the associated side effects. Participants believed that family and friends are most likely to influence this behavior (48%) and perceived that individuals who practice skin lightening do so because this provides a more fashionable look (76%). Men and women were found to be equally likely to use SLPs, and those residing in urban settings are 10 times more likely to engage in the practice compared with rural dwellers. Conclusion: This study contributes valuable information on the phenomenon of skin lightening among a diverse group of young adults. The results highlight the influential role social media platforms and family members play in motivating use of SLPs. Furthermore, the equal likelihood of use among both sexes suggests that the practice is growing among males.